Psikologi Agama Pada Anak Usia Dini Dalam Perspektif Pemikiran Imam Al-Ghazali - Fadhilah, Muthia Nur; Mutmainnah, Mutmainnah (Prodi PIAUD STAI Sumatera Medan, 2024)
This study examines the concept of religious psychology in early childhood from the perspective of Imam Al-Ghazali’s thought, aiming to describe his views, identify the fundamental concepts of religious psychology related to children’s spiritual development, and explore their relevance in the context of modern education. The research employs a qualitative method with a library research approach, analyzing Al-Ghazali’s major works such as Ihya’ Ulum al-Din, Ayyuha al-Walad, and Mizan al-‘Amal. The findings reveal that Al-Ghazali places spirituality at the core of personality development in children through key concepts such as fitrah (innate purity), qalb (heart), tazkiyah al-nafs (purification of the soul), adab (moral habituation), and the integration of knowledge and action. These five concepts form a framework of religious psychology emphasizing the importance of role modeling, habituation, and spiritual purification from an early age. Al-Ghazali’s ideas remain highly relevant in addressing the challenges of globalization and moral decline today, as they promote a holistic form of spiritual education centered on cultivating divine consciousness in children. Theoretically, this research contributes to the development of an Islamic Spiritual Development Framework for Early Childhood, while practically offering guidance for early childhood education institutions to implement curricula grounded in classical Islamic values.